Evaluating Anti-Hypertensive Drugs’ Suitability Based on the Hospital Formulary in the Hospital’s Pharmaceutical Installation - Fitriati, Retno; Chusun, Chusun (International Journal Labs, 2022)
Background: Hypertension is a disease characterized by an increase in blood pressure> 140/90 mmHg. Hypertension patients usually seek treatment using a BPJS card. Medications used for BPJS patients must be in accordance with the established Hospital Formulary. Aim: This study aims to determine the suitability of the use of anti-hypertension drugs based on the Hospital’s Formulary and the Hypertension Therapy Algorithm. Method: This research is a descriptive study with data collection retrospectively with the research instrument being a prescription for hypertension patients. The population in this study was the prescription of Anti-Hypertension drugs in the RS. Jantung Diagram Siloam Cinere – Depok in the period August to October 2015. Findings: From the results of the study there were 50,816 samples of anti-hypertensive drugs for 3 months consisting of August 16,807 drugs, September 16,322 drugs, and October 17687. From these data obtained all patients get a prescription in accordance with Formulary Hospital. Based on the results of the study, it can be concluded that patients who get a prescription according to the Hospital Formulary as much as 100%. From the study results, the authors suggest that doctors of the Siloam Cinere Heart Hospital Depok Depok prescribe Antihypertensive drugs in accordance with the established Hospital Formulary.